Innovative Swimming Activities: Enhancing Self-Confidence, Safety, and Motor Development in Young Children - Dewi, Komang Ayu Krisna; Tutuandari, Ni Komang Rian (Champions: Education Journal of Sport, Health, and Recreation, 2025)
This study aimed to examine the effectiveness of an innovative play-based approach in swimming instruction to enhance self-confidence, water safety awareness, and fundamental motor skills among early childhood learners. The research was conducted at SDN 1 Batuagung, Jembrana, using a quantitative method with a quasi-experimental design—specifically, a non-equivalent control group design—involving 40 students aged 6–8 years. The experimental group received swimming instruction through innovative play-based methods, while the control group received conventional instruction. Instruments included a self-confidence scale based on Bandura’s self-efficacy indicators, a water safety observation sheet adapted from the Life Saving for Kids module (ILSF, 2021), and a water-contextualized version of the TGMD-2 motor skills test. All instruments were validated by experts and demonstrated high reliability (α > 0.80). Data were analyzed using paired sample t-tests and independent sample t-tests with SPSS version 25. The results showed significant improvements in the experimental group compared to the control group: self-confidence increased by 32%, water safety by 43%, and fundamental motor skills by 38%. These findings indicate that the innovative play-based approach creates a safe, enjoyable, and adaptive learning environment. Theoretically, the study contributes to the body of knowledge in physical education and early childhood development, while practically, it provides guidance for teachers, coaches, and curriculum developers to design swimming lessons that are holistic—addressing not only technique, but also psychological and safety aspects. This research also opens avenues for future exploration on the long-term impacts of this model on character building, emotional regulation, and its applicability to children with special needs or outdoor water-based learning environments.